Properties of electron swarm parameters in Tetrahydrofuran - Dr.Mohammad, M. Othman (International Journal of Modern Agriculture, 2021)
Reported electron collision cross sections data in the energy range ~ 0 to 300 eV (see section 3) from gaseous biomolecule Tetrahydrofuran (THF) have been used to calculate the electron energy distribution function and electron (EEDF) and swarm parameters for electrically excited THF, using a two-term solution of the Boltzmann equation. The electron swarm parameters namely ( mean energy, drift velocity, diffusion coefficient, electron mobility, characteristic energy, attachment and ionization coefficient), at room temperature and atmospheric pressure are presented over a wide range of applied electric field strength E/N ( E is the electric field and N is the gas number density) varying from 0.1 to 1000 Td (1Td=10-17 Vcm2). The EEDF found to be non-Maxwellian. The electron swarm parameters are compared with those calculated using multi term kinetic theory and experimentally using the pulsed Townsend technique. The influence of inelastic cross section on the calculated transport parameters is also explained.